2022
DOI: 10.1002/aenm.202202861
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Fine Structure Optimizations of Layered Transition‐Metal Oxide Cathodes for Potassium‐Ion Batteries

Abstract: Potassium‐ion batteries (PIBs) have attracted significant research interest in the context of driving the advancement of grid energy storage due to K's elemental abundance and high theoretical output voltage. The main challenge facing PIBs is to find suitable cathode materials with fast transport kinetics and stable framework structures to intercalate/de‐intercalate the large‐size K+. Among these candidates, transition‐metal layered oxides are have excellent potential and have been extensively exploited due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 187 publications
0
20
0
Order By: Relevance
“…K-ion batteries (KIBs) show the same “rocking chair” working principle as lithium-ion batteries (LIBs), and the K + /K potential (−2.93 V vs standard hydrogen electrode) and Li + /Li potential (−3.04 V vs standard hydrogen electrode) are very close. Additionally, the abundance of potassium (2.09 wt %) in the crust is much higher than that of lithium (0.0017 wt %), and the cost of KIBs is lower than that of LIBs. Furthermore, the Stokes radius of K + (3.6 Å) is much smaller than that of Li + (4.8 Å), which allows the high K + conductivity in liquid electrolyte. , Therefore, KIBs have shown great application potential in the field of electric transportation and large-scale energy storage. …”
Section: Introductionmentioning
confidence: 99%
“…K-ion batteries (KIBs) show the same “rocking chair” working principle as lithium-ion batteries (LIBs), and the K + /K potential (−2.93 V vs standard hydrogen electrode) and Li + /Li potential (−3.04 V vs standard hydrogen electrode) are very close. Additionally, the abundance of potassium (2.09 wt %) in the crust is much higher than that of lithium (0.0017 wt %), and the cost of KIBs is lower than that of LIBs. Furthermore, the Stokes radius of K + (3.6 Å) is much smaller than that of Li + (4.8 Å), which allows the high K + conductivity in liquid electrolyte. , Therefore, KIBs have shown great application potential in the field of electric transportation and large-scale energy storage. …”
Section: Introductionmentioning
confidence: 99%
“…[20,21] To enhance the rate capability and cycling stability, advanced cathode and anode materials with large ion channels and rational structures should be explored. As the Na + /K + ions providers, layered transition metal oxides, [22,23] polyanionic compounds [24,25] and Prussian blue like compounds [26,27] have been successfully designed, referring to those in LIBs. As for the anode material, the commercial anode of graphite in LIBs is unable to extend in the SIBs and PIBs, attributed to the thermodynamic reason and limited interlayer spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium-ion batteries (PIBs) have tremendous potential as post-lithium-ion energy storage systems due to their lower cost, abundant potassium reserves, and low redox potential (−3.04 V vs. SHE for Li + /Li, −2.94 V vs. SHE for K + / K). [1][2][3] It has been demonstrated that graphite anodes are viable in PIBs. However, the theoretical capacity of graphite is only 279 mA h g −1 .…”
Section: Introductionmentioning
confidence: 99%